Regulating Work from Home to Promote Work-Life Balance: A Comparative Legal Review of Malaysia, the UK and Australia - Ruzita Azmi; Zurina Adnan; Rosmawani Che Hashim; Siti Nur Samawati Ahmad (Sriwijaya Law Review, 2026)
The traditional office-based model of employment has undergone a significant transformation as flexible working arrangements (FWAs) and remote work have become increasingly prevalent. This development has been influenced by technological progress and evolving societal expectations regarding work-life balance (WLB). In many Commonwealth countries, such as Malaysia, the COVID-19 pandemic catalysed the widespread adoption of flexible and remote work arrangements. As lockdowns and social distancing measures forced businesses to adapt, many organisations discovered the viability and effectiveness of remote work, particularly working from home (WFH). This paper aims to examine the legal framework and policies or best practices in Malaysia that promote WLB and facilitate WFH options, and to compare these policies or best practices and legal frameworks with those in developed commonwealth countries such as the UK and Australia. This paper applies doctrinal research and comparative methods. The doctrinal or library research comes from textbooks, reports and articles from law and non-law journals and reviews. Doctrinal research aims to understand the principles of law and policies dealing with FWA and WFH options. A comparative study will be employed to examine similarities and differences across situations within the same commonwealth legal system. The paper concludes that, to promote WLB and facilitate the WFH option through FWA, a comprehensive legal framework and effective policies are required, especially in Malaysia .